Labor regulations in Peru for adolescents, and regulatory effectiveness - Bobadilla Yzaguirre, Magali Beatriz (2020)
The aim of this study is to expose the reality of adolescent labor in Peru. Adolescent workers aged fourteen have been the object of regulatory protection for around one hundred years in Peru; however, although our standards of protection have been brought in line with the global context through international conventions, an adequate exercise of rights on the part of interested parties has not been achieved, and the result has been the generating of an informal labor market. This has occurred in spite of the existence of valid legal norms that meet accepted standards of effectiveness, but which in reality do not offer the progress being sought.